POWER AND SOLIDARITY REFLECTED IN THE USE OF PRONOUNS PORTRAYED IN HYBRID POLITICAL DISCOURSE - Muh Fajar (STKIP PGRI Jombang, 2019)
This research examined power and solidarity reflected in the use of pronouns in President Barrack Obama’s presidential speech at the University of Indonesia by applying critical discourse analysis. The speech can be called as a hybrid political discourse individual because he was a hybrid, an ex-Indonesian. Power and solidarity in hybrid political discourse can be explored by analysing language usage in speech and wordings in speech texts. Furthermore, the analysis of language usage to examine power and solidarity has a close relation to ideology. Power and solidarity are like two sides of a coin. There will be an ambiguity of determing power or solidarity used by one participant to another in delivering utterances. Power and solidarity were linguistically expressed by President Obama in his speech at University of Indonesia in the use of pronouns. He used power to show America’s hegemony toward Indonesia and solidarity to to minimize the gab between America and Indonesia. President Obama used power and solidarity in order that Indonesian people will accept him (America) as friend, to show that there is no fight between America (western people/christian) and Indonsia (moslem world). Moreover, Obama applied these expressions are to secure the America’s politics against for terrorism, America wanted that Indonesia will be its friend to fight terrorism and moslem radicals, and Indonesia will be a big new markets for the American’s goods. Thus, the phenomenon of solidarity, in this sense, cannot be meant only that President Barrack Obama was familiar and close with Indonesia people, but he has another agenda in order that the US interests in Indonesia will be accepted by The Indonesian People. Furthermore, Obama has any concessions that he should do this in order to ‘demonstrate’ that America would like to teach their moral, their ideas, their values and political leadership in the general public, particulary their central claim to political legitimacy.